“It’s Disgraceful Going through All this for Being an Arab and Disabled”: Intersectional and Ecological Barriers for Arabs with Disabilities in Israel - Leena Badran (17916473) (2023)
The current study examines the perspectives of Arabs with disabilities living in Israel coping with various barriers as ethnic and political minority group members who also have disabilities. Our qualitative study utilized a grounded theory approach. Thematic analysis of in-depth interviews was conducted among 15 Arabs with physical, visual impairment, and mental disabilities. Three major themes were derived from the participants’ responses: microsystem, exosystem, and macrosystem, with each in turn having several sub-themes. A unique model was developed to integrate intersectional and ecological theories. Applying this integrative model, a reverse ratio was found between the two identity statuses of minority and disability. Moving toward the outer levels of an ecological model (macrosystem), the influence of ‘minority identity’ strengthened, and that of ‘disability identity’ weakened. The findings conclude that greater political commitment is required by Israel to develop laws and policies that can reduce social opportunity disparities for individuals with minority and disability identity statuses. Other Information Published in: Scandinavian Journal of Disability Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.16993/sjdr.1002